Marine Tourism-Based Sustainable Community Empowerment Model in the New Normal Era - ROMBE, Elimawaty; ZAHARA, Zakiyah; ADAM, Rosida P.; SUARDI, Suardi; WAHYUNINGSIH, Wahyuningsih; TAUFAL, Moh. (Journal of Environmental Management and Tourism, 2023)
Community-based tourism is an empowerment approach that involves and places the community as an important public in the context of the new sustainable development paradigm. Community-based tourism is an opportunity to mobilize the potential and dynamics of the community, in order to balance the role of large-scale tourism business actors. This study aims to determine the Model of Marine Tourism-Based Sustainable Community Empowerment in the New Normal Era. This research is descriptive and quantitative. The study used a purposive sampling method with 100 samples with a questionnaire to the community in Palu City and Donggala Regency. This data was analyzed using Partial Least Square (PLS). The results showed that the variable of community-based tourism, where the variables of economy, culture, social, political environment had a significant effect on community development. It states that community empowerment refers to how local communities have a great influence socially and in community organizations to improve their living environment.